Superconvergence for Triangular Linear Edge Elements (Communications in Computational Physics, 2018)
Superconvergence for the lowest-order edge finite elements on strongly regular triangulation is studied. By the averaging technique, superconvergence of orderO(h2) is established at the midpoint of the interior edge for both the finite elementsolution and the curl of the finite element solution. Numerical results justifying ourtheoretical analysis are presented.
Keywords: Maxwell's equations; superconvergence; FEM; strongly regular grid; edge elements.